1998
DOI: 10.1094/mpmi.1998.11.12.1258
|View full text |Cite
|
Sign up to set email alerts
|

Differential Display Analysis of the Early Compatible Interaction Between Soybean and the Soybean Cyst Nematode

Abstract: The marked cellular changes during feeding site formation of the soybean cyst nematode (Heterodera glycines) indicate major changes in soybean gene expression. We used differential display of mRNA to detect host gene expression changes during the early compatible interaction between soybean and H. glycines. Fifteen cDNA clones corresponding to mRNAs with different abundances in H. glycines-infected versus uninfected roots were identified. Differential display results indicated that abundances of five mRNAs inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 26 publications
0
60
0
Order By: Relevance
“…As molecular biology techniques improved, PCR enrichment strategies were employed to identify transcripts directly from cDNA libraries in response to nematode infections. Frequently, whole root systems were used as a starting material for RNA isolation (Hermsmeier et al 1998 ;Mahalingam et al 1999 ;Vaghchhipawala et al 2001) . Furthermore, chances of identifying genes that were differentially regulated by nematode infections were improved by collecting tissues enriched for nematode feeding sites using approaches of preselecting infested tissues (for example, giant-cell or syncytial containing tissues) (Hermsmeier et al 2000 ;Vercauteren et al 2001) , by manually dissecting feeding sites or by microaspiration (Wieczorek et al 2006) .…”
Section: Early Methods Analyzing Gene Expression During Nematode Paramentioning
confidence: 99%
See 1 more Smart Citation
“…As molecular biology techniques improved, PCR enrichment strategies were employed to identify transcripts directly from cDNA libraries in response to nematode infections. Frequently, whole root systems were used as a starting material for RNA isolation (Hermsmeier et al 1998 ;Mahalingam et al 1999 ;Vaghchhipawala et al 2001) . Furthermore, chances of identifying genes that were differentially regulated by nematode infections were improved by collecting tissues enriched for nematode feeding sites using approaches of preselecting infested tissues (for example, giant-cell or syncytial containing tissues) (Hermsmeier et al 2000 ;Vercauteren et al 2001) , by manually dissecting feeding sites or by microaspiration (Wieczorek et al 2006) .…”
Section: Early Methods Analyzing Gene Expression During Nematode Paramentioning
confidence: 99%
“…A differential display analysis comparing transcript abundance in H. glycines infested and noninfested soybean roots identified 15 gene transcripts that were differentially regulated one day after inoculation (Hermsmeier et al 1998) . To identify nematode-regulated transcripts, Hermsmeier and colleagues used primers that were specially designed to amplify random cDNAs from infested and control libraries.…”
Section: Early Gene Expression Analyses Of Whole Infested Rootsmentioning
confidence: 99%
“…The magnitude of the changes in soybean during SCN-infection suggests that many genes are involved. Several genes related to SCN-infection have been identified in soybean, including those encoding polygalacturonases [3], an ethylene-responsive element-binding protein [4], a phosphoribosylformyl-glycinamidine synthase [5], an extension [6], a cyclin [7], a GTP-binding protein [8], etc. In recent years, several studies profiling global soybean responses to SCN infection using differential display and microarray approaches have increased our understanding of changes in gene expression during SCN-infection [9][10][11][12].…”
mentioning
confidence: 99%
“…In an earlier investigation, Hermsmeier et al (1998) used differential display of mRNA to detect host gene expression changes during the early compatible interaction between soybean and SCN. The authors identified 15 genes with different expressions in SCN-infected versus uninfected roots.…”
Section: Transcriptome Analyses Of Nematode Resistances In Soybeanmentioning
confidence: 99%
“…The authors identified 15 genes with different expressions in SCN-infected versus uninfected roots. Of those, the ADR12 gene was identified to be involved in soybean auxin downregulation, suggesting that the auxin pathway may be involved in soybean-nematode interaction (Hermsmeier et al 1998).…”
Section: Transcriptome Analyses Of Nematode Resistances In Soybeanmentioning
confidence: 99%